Pengembangan Aplikasi Edukasi Pengenalan Pohon Berbasis Qr Code Scanner - Mohammad Reza Faisal; Radityo Adi Nugroho; Friska Abadi (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2023)
Natural tourist areas certainly have a variety of biodiversity that can be used as a place for education. Many types of trees can be found in the area, such as Beringin, Jeruju, Jingah, Nipah, and so on. However, the collection of data about trees has not been properly recorded and there is no comprehensive information about the trees there, so that when visitors travel there it will be difficult to identify them. Therefore, in an effort to help overcome existing problems, it is necessary to develop technology with QR Codes to be able to identify trees in natural tourism parks. The stages of implementing the service are creating an application where this application is made in the form of a website-based information system and socializing the use of the tree recognition educational application. The goal to be achieved is to create a website-based application for recognizing trees, so that visitors, whether they come directly or just want to see the tree collection in the natural tourism park but are constrained by distance, time, etc., visitors can access via a web browser on smartphones, laptops, etc. and personal computers wherever they are provided there is an internet connection.